Short Communication: Genetic diversity of Indonesian’s sugarcane varieties (Saccharum officinarum) based on RAPD molecular markers (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kasiamdari RS, Aristya GR, Prabowo H, Ariesta C, Arif MF. 2019. Genetic diversity of Indonesian’s sugarcane varieties (Saccharum officinarum) based on RAPD molecular markers. Biodiversitas 20: 3005-3010. Sugarcane (Saccharum officinarum L.) belongs to the Poaceae family which are widely used for sweeteners production. In Indonesia, the need for sugarcane continues to increase along with its increased use in the production of bioethanol from molasses, a by-product of sugar production. However, the supply for sugar is still far from enough. Improvement of sugarcane productivity can be done by selecting superior varieties to form a new superior hybrid. Maintaining high genetic diversity in a population is essential. Selection of varieties is important because it can increase productivity without increasing the cost of crop production. Even the selected pest-resistant varieties can reduce the cost of crop production. Indonesia had produced many superior sugarcane plant varieties, but studies on their characters and genetic relationship are still lacking. Several molecular markers have been used to elucidate the genetic diversity among sugarcane varieties. Random Amplified Polymorphism DNA (RAPD) is one of the molecular markers that have been proven to describe genetic diversity among sugarcane plants. This study aimed to determine the genetic diversity among 22 superior sugarcane varieties in Indonesia based on eight RAPD molecular markers. The superior sugarcane varieties in Indonesia in this study were obtained from Indonesian Sweetener and Fiber Crops Research Institute (ISFRI), Malang and Madukismo Sugar Factory, Yogyakarta. DNA products were visualized by using gel electrophoresis and resolved bands were scored as binary data as presence (1) and absence (0). Linkage distance was done based on Jaccard’s similarity coefficient, and clustering analysis was performed based on the unweighted pair- group average (UPGMA) method. Polymorphism Information Content (PIC) analysis showed a high degree of polymorphism ranging from 0.76 to 0.92. Cluster analysis showed that 22 sugarcane varieties were divided into two main clusters and four sub-clusters based on their origin.
Keywords: Clustering, genetic diversity, polymorphism, RAPD, Saccharum officinarum